Attribute-Aware Recommender System Based on Collaborative Filtering: Survey and Classification - Chen, Wen-Hao; Hsu, Chin-Chi; Lai, Yi-An; Liu, Vincent; Yeh, Mi-Yen; Lin, Shou-De (Frontiers in Big Data, 2020)
Attribute-aware CF models aims at rating prediction given not only the historical rating from users to items, but also the information associated with users (e.g. age), items (e.g. price), and ratings (e.g. rating time). This paper surveys works in the past decade developing attribute-aware CF systems, and discover that mathematically they can be classified into four different categories. We provide the readers not only the high level mathematical interpretation of the existing works in this area but also the mathematical insight for each category of models. Finally, we provide in-depth experiment results comparing the effectiveness of the major works in each category.